2018
DOI: 10.1177/2167702618807408
|View full text |Cite|
|
Sign up to set email alerts
|

The Multilevel Structure of Daily Emotion-Regulation-Strategy Use: An Examination of Within- and Between-Person Associations in Naturalistic Settings

Abstract: Existing structural analyses of emotion-regulation (ER) strategies have relied on retrospective, dispositional assessments, ignoring the within-person structure (i.e., intraindividual strategy groupings based on momentary covariances) and variability in strategy use across time and contexts. We conducted multilevel exploratory factor analyses on self-reported daily use of 11 strategies (i.e., acceptance, behavioral avoidance, distraction, experiential avoidance, expressive suppression, procrastination, reappra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
85
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(98 citation statements)
references
References 66 publications
6
85
0
Order By: Relevance
“…Researchers have demonstrated that a multitude of factors can influence a given strategy's effectiveness (e.g., situational goals; English et al, 2017; perceived controllability of a stressor; Haines et al, 2016; timing of strategy use; Kalokerinos et al, 2017), which may call into question whether strategies can be reliably distinguished as adaptive or maladaptive. However, researchers studying BPD, and psychopathology more broadly, have consistently found empirical evidence that putatively adaptive and putatively maladaptive strategies can be differentiated based on individual differences (e.g., Aldao & Nolen-Hoeksema, 2012;Naragon-Gainey et al, 2017;Neacsiu et al, 2010;Southward & Cheavens, 2020) and within-person patterns of use (e.g., McMahon & Naragon-Gainey, 2019). People with BPD in particular have demonstrated the ability to use strategies that are both effective at reducing negative emotions in the short-term and maladaptive in the long-term (e.g., self-harm; Carpenter & Trull, 2013;Putnam & Silk, 2005).…”
Section: Behavioral Responses To Emotions In Bpdmentioning
confidence: 99%
“…Researchers have demonstrated that a multitude of factors can influence a given strategy's effectiveness (e.g., situational goals; English et al, 2017; perceived controllability of a stressor; Haines et al, 2016; timing of strategy use; Kalokerinos et al, 2017), which may call into question whether strategies can be reliably distinguished as adaptive or maladaptive. However, researchers studying BPD, and psychopathology more broadly, have consistently found empirical evidence that putatively adaptive and putatively maladaptive strategies can be differentiated based on individual differences (e.g., Aldao & Nolen-Hoeksema, 2012;Naragon-Gainey et al, 2017;Neacsiu et al, 2010;Southward & Cheavens, 2020) and within-person patterns of use (e.g., McMahon & Naragon-Gainey, 2019). People with BPD in particular have demonstrated the ability to use strategies that are both effective at reducing negative emotions in the short-term and maladaptive in the long-term (e.g., self-harm; Carpenter & Trull, 2013;Putnam & Silk, 2005).…”
Section: Behavioral Responses To Emotions In Bpdmentioning
confidence: 99%
“…Across college students and bereaved adults, the ability to both up-and down-regulate facial expressions of emotion in response to explicit environmental demands predicted decreases in depression and anxiety severity one month to three years later (Bonanno et al, 2004;Coifman & Bonanno, 2010;Southward & Cheavens, 2017;Westphal et al, 2010). Using ecological momentary assessment (EMA), the within-person use of a greater variety of adaptive strategies was associated with greater momentary positive affect (Roesch et al, 2010) and lower momentary negative affect, dysphoria, and social anxiety in community, but not clinical, samples (McMahon & Naragon-Gainey, 2019). However, other researchers have found that using a wider variety of emotion regulation strategies across situations (Dixon-Gordon et al, 2015) and within situations (Aldao & Nolen-Hoeksema, 2013;Brans et al, 2013;Southward et al, 2018) is associated with greater psychopathology, personality dysfunction, and negative affect.…”
Section: Basic Science Research On Emotion Regulation Skill Use and Ementioning
confidence: 99%
“…However, among people with elevated social anxiety, neither the use of more strategies nor perceived effectiveness of those strategies was related to daily social anxiety (Kivity & Huppert, 2016). Of note, although each of these studies conducted longitudinal analyses, only two (McMahon & Naragon-Gainey 2019;Roesch et al, 2010) explicitly disaggregated between-from within-person effects. The results of these studies thus may be driven more by stable individual differences (between-person effects) than unique temporal relations (within-person effects).…”
Section: Basic Science Research On Emotion Regulation Skill Use and Ementioning
confidence: 99%
“…The current effectiveness ratings were also aggregated across situations given the number of observations, reducing chances to evaluate contextual influences on ER effectiveness. Further, although running analyses at the cluster‐level allows for comparison of current findings with previous cluster‐level findings from the literature (e.g., McMahon & Naragon‐Gainey, ), opportunities for strategy‐specific conclusions are necessarily limited when clustering. Replications within college student samples and extensions to other populations will also be important to evaluate generalizability of these findings.…”
Section: Conclusion and Limitationsmentioning
confidence: 99%
“…To reduce the number of tests and more broadly characterize the effectiveness of strategies that are often considered adaptive versus maladaptive, the eight strategies were classified into either engagement-or avoidance-oriented clusters, according to a principal component analysis (KMO = 0.614, p < .0001; Hutcheson & Sofroniou, 1999), described in greater detail in Daros et al (2019). A similar clustering approach, which also found two factors named Engagement and Avoidance across 11 ER strategies, was recently used by McMahon and Naragon-Gainey (2018).…”
Section: Er Strategiesmentioning
confidence: 99%